DEVELOPMENT OF ANDROID-BASED “MBARENGI” STATISTICS E-MODULE AS AN INNOVATION FOR STATISTICS LEARNING MEDIA WITH HYBRID LEARNING - Astuti, Cindy Cahyaning; Wiguna, Akbar; Latifa, Fitri Nur; Olvyya, Amaydhi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The learning process is closely related to the interaction between educators and students. In order to facilitate the learning process, educators are required to make learning more innovative in order to be able to encourage students to study hard and be able to follow the learning process well. One of the innovations that can be done in the learning process is innovation in learning media. Learning media is one of the components of learning that has an important role in teaching and learning activities, especially in the transition after the Covid 19 pandemic. The use of smartphones can be one of the innovations of learning media by using Android-based e-modules. This research is development research or called Research and Development (R&D) using the ADDIE development model (Analyze, Design, development, Implementation, and Evaluation). The Android-based "MBARENGI" Statistics E-Module was validated by material experts, learning media experts, and tested on a limited scale sample. The results of the validation of material experts on the aspect of content material are 91.5% and on the language aspect are 93.2%. The results of media expert validation on the aspect of content quality are 92.3%, on design and audio aspects are 94.4% and the interaction and feedback aspects are 92.3%. In the test results, student responses obtained an average result are 88.8% which stated that the Android-based "MBARENGI" Statistics E-Module was feasible to be used in the learning process.